PENERAPAN THE MAGICAL READING BOOK UNTUK MENINGKATKAN KETERAMPILAN MEMBACA KELAS II SDN SUKUN 1 MALANG - sari, Diana; Suwito; Cicilia Ika Rahayu Niat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reading skills are fundamental competencies that support students’ learning success in elementary school. Based on observations conducted in Grade II of SDN Sukun 1 Malang, several students experienced difficulties in recognizing letters, reading syllables, words, and simple sentences. This study aimed to improve students’ reading skills through the implementation of The Magical Reading Book. The study employed Classroom Action Research (CAR) conducted in two cycles involving 26 Grade II C students. Data were collected through observation, tests, and documentation. The results showed that the implementation of The Magical Reading Book improved students’ reading skills. Learning mastery increased from 76% in the first meeting of Cycle I to 92% in the second meeting. In Cycle II, learning mastery improved from 92% to 100%. The average class score also increased from 90 to 96. These findings indicate that The Magical Reading Book is an effective learning medium for improving elementary school students’ reading skills.